Odonata from La Pampa province, Argentina - del Palacio, Alejandro (2017)
In Argentina approximately 280 odonate species have been recorded, which are chiefly found in the north-eastern and north-western regions. With only three previously recorded species, La Pampa province is one of most understudied parts of the country. In the present work we provide a check-list of 17 species from La Pampa, including 14 new records for the province.